Intellectuals and the public good : creativity and civil courage - Misztal, Barbara A. (Cambridge University Press, 2007)
Creativity and civil courage are major dimensions of an intellectual's authority and contribute towards the enrichment of democracy. This book develops a sociological account of civil courage and creative behaviour in order to enhance our understanding of the nature of intellectuals' involvement in society. Barbara A. Misztal employs both theoretical-analytic and empirical components to develop a typology of intellectuals who have shown civil courage and examines the biographies of twelve Nobel Peace Prize laureates, including Elie Wiesel, Andrei Sakharov and Linus C. Pauling, to illustrate acts of courage which have embodied the values of civil society. She advances our understanding of the nature of intellectuals' public involvement and their contribution to social well-being. In the current climate of fear and insecurity, as governments are forced to deal with issues of increasing complexity, this is a pioneering sociological book with a highly original approach.